CHARACTERISTICS OF THE PROCESSES OF FREE RADICAL OXIDATION AND THE ACTIVITY OF ANTIOXIDANT PROTECTION ENZYMES IN PATIENTS WITH DIFFUSELY TOXIC GOITER ON THE BACKGROUND OF CORRECTIVE THERAPY WITH IODINE-SACCHARIDE COMPLEX (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Studies have been conducted to study and characterize the features of free radical oxidation processes and the activity of antioxidant protection enzymes in patients with diffusely toxic goiter on the background of corrective therapy with an iodine-saccharide complex. The study included 154 patients with a diagnosis of diffuse toxic goiter treated with mercazolil. It was revealed that against the background of corrective therapy, the functional state of the liver is impaired and oxidative stress increases depending on the duration of corrective therapy, manifested by the intensive involvement of the glutathione redox system in the process of antioxidant protection.